PROGESTERONE PROFILE IN TWO DIFFERENT PROTOCOLS OF ESTRUS SYNCHRONIZATION IN POST PARTUM RED KANDHARI COWS - DESHMUKH, Y D; MARKANDEYA, N M; CHAUDHARl, R J; DESHMUKH, V V (The Indian Journal of Animal Reproduction, 2023)
Thirty six post-partum Red Kandhari cows were selected and randomly divided into two groups i.e. protocol group I (Select synch) and Protocol Group-II (Ovsynch) comprising twelve animals each and control Groups Ill and IV comprising six animals each. Protocol group animals were administered with injection GnRH 1 00μg intramuscularly on day 1st followed by injection PGF2 526μg intramuscularly on day 7th. Second injection of GnRH 100μg was administered intramuscularly only in protocol group II on day 91h and after 16-22 hrs of second GnRH injection, fixed time inseminations were carried out whereas in protocol group I, animals confirmed in estrus were bred by Al at appropriate times. The mean serum progesterone level of cows on day 1•1, 71ti, 91h and 19th of the trial in protocol group I was 01.80, 02.90, 01.10, 04.20 and in protocol group ll the same was 01.90, 03.60, 01.10 and 06.84 ng/ml on day 1 •t, 71 9t11and19’h whereas in control groups iii and IV, the level was 2.5, 2.4, 2.3, 2.4 and 2.5, 2.4, 2.3, 2.5 ng/ml respectively. The difference in the level of progesterone was non-significant throughout the experiment in control group animals. Selectsynch protocol in Red Kandhari cows was effective to induce estrus with 66.67 per cent efficacy and 87.50 per cent conception rate and 58.33 per cent pregnancy rate, whereas ovsynch protocol was successful to induce estrus with 66.67 per cent efficacy with 50.00 per cent conception rate and pregnancy rate.